Empowering the community and professional development through collaborative digital learning - Hoo, Choon Lih; Poh, Wei Lin; Tierney, Anne Margaret (Penerbit Universiti Kebangsaan Malaysia, 2022)
The global pandemic situation has shifted physical learning to online professional development to be challenging. This is particularly difficult to ensure effective psychomotor learning when learners are disconnected from the conventional peer interaction and physical hardware. This promoted the importance of resilience for both educators and learners to reconnect psychomotor learning through virtual/hybrid setting. A staff-student collaborative inspiration emerged with the collaboration across Malaysia and Edinburgh campuses in engaging multiple learning styles through remote digital learning. Aligned to the rising call of building innovation-entrepreneurship ecosystem, this student-led project focused on remote development of programming skills, translating ideas into tangible solution, and pitching among Malaysia and international students to address a selected Sustainable Development Goal. This inter-disciplinary initiative connects the field of engineering and psychology in studying the resilience context of learning. A resilience theme focuses on enhancing skills through digital platforms in building resilient communities. A total of 45 local and international students were engaged through an online prototype and idea pitching competition that supported by industrial workshops. A survey and thematic analysis were launched to gather the feedback from students upon completion of the project. The outcomes highlight the positive response from students’ perspective as participants and judges, and their learning growth. The studied themes indicate the effectiveness of learning through hardware/physical aspect on cognitive, psychomotor, and affective learning domains. This project remarks a cross academic fields (engineering and psychology), sectors (academy and industry), countries (Malaysia and Edinburgh), and roles (educators and learners) inter-disciplinary team effort.